Hubungan aktivitas senam dengan kadar trigliserida pada pasien wanita di laboratorium klinik Prodia Samarinda: Indonesia - Tetiteti Rachmawati; Hari Saktiningsih (Universitas Widya Gama Mahakam Samarinda, 2022)
Background: Hypertriglyceridemia is a condition characterized by increased triglyceride levels >150 mg/dl. Gymnastics is a form of physical exercise that is systematic, regular, and planned by performing specific movements to benefit the body. This gymnastic activity is a form of endurance exercise that can increase lipoprotein lipase (LPL) activity in muscle and adipose tissue, increasing the breakdown of lipoproteins rich in triglycerides. During exercise, the activity of lipoprotein lipase, which breaks down triglycerides, increases. Objectives: This study aims to determine the relationship between exercise activity and triglyceride levels in female patients at the Prodia Samarinda clinical laboratory. Research Metodes: This research is observational analytic research with a cross-sectional approach. The sampling technique used quota sampling with 47 samples of research subjects. Results: This study obtained data on the correlation coefficient between exercise and triglyceride levels -0.436. The value of the gymnastic sig. with triglyceride levels was 0.002. Meanwhile, the direction of the relationship between exercise and triglyceride levels is negative (inversely proportional).